Drug abuse: concepts, prevention, and cessation - Sussman, Steve (Cambridge Univ. Press, 2008)
Concepts and classes of drugs -- Concepts of drug, drug use, misuse, and abuse -- Further classifications relevant to substance abuse and dependence -- Types of drugs, history of drug use and misuse, and costs of drug misuse -- Current multivariable models -- Neurobiologically-relevant -- Cognitive processes -- Social interaction and social groups -- The large social and physical environment -- Assessment -- Concepts of prevention -- Neurobiologically relevant -- Cognitive processes -- Social interaction and social groups -- The large social and physical environment -- Concepts of cessation -- Neurobiologically-relevant -- Cognitive processes -- Social interaction and social groups -- The large social and physical environment -- Conclusions, and recent and future directions